Gpr158 Deficiency Impacts Hippocampal CA1 Neuronal Excitability, Dendritic Architecture, and Affects Spatial Learning - Çetereisi, Demirhan; Kramvis, Ioannis; Gebuis, Titia; van der Loo, Rolinka J.; Gouwenberg, Yvonne; Mansvelder, Huibert D.; Li, Ka Wan; Smit, August B.; Spijker, Sabine (Frontiers in Cellular Neuroscience, 2019)
G-protein-coupled receptor 158 (Gpr158) is highly expressed in striatum, hippocampus and prefrontal cortex. It gained attention as it was implicated in physiological responses to stress and depression. Recently, Gpr158 has been shown to act as a pathway-specific synaptic organizer in the hippocampus, required for proper mossy fiber-CA3 neurocircuitry establishment, structure, and function. Although rodent Gpr158 expression is highest in CA3, considerable expression occurs in CA1 especially after the first postnatal month. Here, we combined hippocampal-dependent behavioral paradigms with subsequent electrophysiological and morphological analyses from the same group of mice to assess the effects of Gpr158 deficiency on CA1 physiology and function. We demonstrate deficits in spatial memory acquisition and retrieval in the Morris water maze paradigm, along with deficits in the acquisition of extinction memory in the passive avoidance test in Gpr158 KO mice. Electrophysiological recordings from CA1 pyramidal neurons revealed normal basal excitatory and inhibitory synaptic transmission, however, Schaffer collateral stimulation yielded dramatically reduced post-synaptic currents. Interestingly, intrinsic excitability of CA1 pyramidals was found increased, potentially acting as a compensatory mechanism to the reductions in Schaffer collateral-mediated drive. Both ex vivo and in vitro, neurons deficient for or with lowered levels of Gpr158 exhibited robust reductions in dendritic architecture and complexity, i.e., reduced length, surface, bifurcations, and branching. This effect was localized in the apical but not basal dendrites of adult CA1 pyramidals, indicative of compartment-specific alterations. A significant positive correlation between spatial memory acquisition and extent of complexity of CA1 pyramidals was found. Taken together, we provide first evidence of significant disruptions in hippocampal CA1 neuronal dendritic architecture and physiology, driven by Gpr158 deficiency. Importantly, the hippocampal neuronal morphology deficits appear to support the impairments in spatial memory acquisition observed in Gpr158 KO mice.